Study on the effect of nitrogen ion implantation process on the bending fatigue strength of carburized and quenched gear - ZHANG Wei; JIA Huapo; GUAN Rongxin; WANG Xiaopeng; MA Chengtian; XU Yaowei (Jixie qiangdu)
Aiming at optimizing the gear surface modification process, the influence of ion nitrogen implantation on the bending fatigue strength of carburized and quenched gears was studied.Using low-carbon alloy steel 18CrNiMo7-6 carburized and quenched gears as the matrix, nitrogen ion implantation treatment was carried out through a radio-frequency plasma-assisted ion implantation system. The root metallography, hardness gradient, residual stress distribution, and bending fatigue properties of ion-implanted gears and unimplanted gears were systematically compared. The results show that the ion nitrogen implantation process increases the root hardness from 695 HV0.1 to 780 HV0.1, an increase of 12.2%; the hardened layer depth decreases from 1.50 mm to 1.41 mm, a reduction of 6.0%; and the surface residual stress decreases from -400 MPa to -286 MPa, a reduction of 28.5%. Based on the R-S-N equation fitted by bending fatigue tests, under 99% reliability, the fatigue life of ion-implanted gears is only 12.3%-19.3% of that of the control gears, with the failure mode dominated by brittle fracture and accelerated crack propagation rate. The study indicates that although ion nitrogen implantation can delay crack initiation through surface strengthening, the excessively shallow hardened layer and reduced residual stress lead to insufficient crack propagation resistance, ultimately weakening the bending fatigue life of gears.